Isolation of enzyme cDNA clones by enzyme immunodetection assay: isolation of a peptide acetyltransferase. - Eberwine, J H (1987)
The biological activity of many proteins and peptides can be profoundly affected by enzyme-catalyzed covalent modifications such as acetylation, sulfation, glycosylation, or amidation. This article describes the cloning of such an enzyme, a peptide acetyltransferase from rat brain that catalyzes the amino-terminal acetylation of endorphins and perhaps other substrates in vivo. Blot-hybridization analysis suggests that the mRNA encoding the acetyltransferase is approximately 2.0 kilobases, is present in whole rat brain and rat hypothalamus, and is slightly larger in mouse AtT20 tumor cells. The acetyltransferase was cloned by using a strategy whereby a cDNA expression library was screened with a solid-phase enzyme-activity assay; this technique combines the use of the substrate coupled to a solid support and subsequent recognition of the product by using a specific antiserum. We have called this method the enzyme immunodetection assay (EIDA). The EIDA should prove useful in the isolation of other clones for proteins that possess enzymatic activity upon expression in bacterial hosts.